2016
DOI: 10.1007/s11119-016-9435-z
|View full text |Cite
|
Sign up to set email alerts
|

Apparent electrical conductivity measurements in an olive orchard under wet and dry soil conditions: significance for clay and soil water content mapping

Abstract: Mediterranean olive trees traditionally grow under rainfed conditions, on poor soils with steep slopes. Rainfall is mainly concentrated during autumn and winter and is characterized by intense rain pulses, separated by dry periods. The use of electromagnetic induction (EMI) techniques in these olive orchards might be questioned since EMI surveys are generally recommended to be performed under moist soil conditions. A 6.7 ha olive orchard was surveyed for EMI-based apparent electrical conductivity (ECa), both u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 29 publications
3
23
0
Order By: Relevance
“…Temporal stability in ECa data has been demonstrated using Spearman rank correlation (De Caires et al, 2015), correlation coefficient between ECa in dry and wet soil conditions (Farahani et al, 2004;Pedrera-Parrilla et al, 2016;Serrano et al, 2013), and map comparisons (Li et al, 2007). One effective method of studying temporal stability of spatially and temporally variable soil properties consists in using principal component analysis (PCA) .…”
Section: Introductionmentioning
confidence: 99%
“…Temporal stability in ECa data has been demonstrated using Spearman rank correlation (De Caires et al, 2015), correlation coefficient between ECa in dry and wet soil conditions (Farahani et al, 2004;Pedrera-Parrilla et al, 2016;Serrano et al, 2013), and map comparisons (Li et al, 2007). One effective method of studying temporal stability of spatially and temporally variable soil properties consists in using principal component analysis (PCA) .…”
Section: Introductionmentioning
confidence: 99%
“…We suspect that those decisions are made in the absence of high-quality information about spatial soil properties in the near subsurface. In this work we have shown that EOF analysis of timelapse EMI provides a key and often missing soil covariate [Pedrera-Parrilla et al, 2016]. We found ECa EOF1 to be a good predictor of spatial soil inventories, reducing cross-validation RMSE by 30.5% in clay weight percent, and 29.5% in total soil carbon weight percent ( Figure 5 and Table S5) using regression kriging versus linear interpolation.…”
Section: Environmental Controls Of Soil Propertiesmentioning
confidence: 77%
“…As an alternative strategy, here we investigate the correlation between the EMI survey results with the 2011 soil core data set. While this strategy is not new [ Pedrera‐Parrilla et al , ], here we argue that the EOF/EC pairs from the time‐lapse imagery will be better environmental covariates with soil properties as individual EMI surveys are known to be affected by soil temperature, soil water content, pore water pH, etc. [ Friedman , ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ECa can be intensively recorded in a parcel, in an easy and inexpensive way, by means of different electrical conductivity sensors currently on the market (e.g. Pedrera-Parrilla et al, 2016).…”
Section: Introductionmentioning
confidence: 99%